2018
DOI: 10.1186/s12905-018-0599-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between self-reported physical activity (IPAQ-SF) and pedometer among overweight and obese women in the MyBFF@home study

Abstract: BackgroundSeveral methods have been developed to determine a person’s physical activity level. However, there is limited evidence in determining whether someone is physically active or not. This study aims to determine the level of physical activity and to compare the usage of short version International Physical Activity Questionnaire (IPAQ-SF) and pedometer among overweight and obese women who were involved in the My Body is Fit and Fabulous at home (MyBFF@home) study.MethodsBaseline and sixth month data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
0
12
0
4
Order By: Relevance
“…These results are consistent with studies conducted among other sub-populations in Malaysia. For example, in a sample of overweight and obese women in Malaysia, 61.1% of them were categorised as physically active when the assessment was conducted using self-reported measures, but only 8.4% were categorised as being sufficiently active via objective measurement method using pedometers [22]. Soon and colleagues used the Lifecorder e-Step accelerometer to measure the total number of steps per day and the total energy expenditure in a sample of office workers in a public university in Malaysia [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results are consistent with studies conducted among other sub-populations in Malaysia. For example, in a sample of overweight and obese women in Malaysia, 61.1% of them were categorised as physically active when the assessment was conducted using self-reported measures, but only 8.4% were categorised as being sufficiently active via objective measurement method using pedometers [22]. Soon and colleagues used the Lifecorder e-Step accelerometer to measure the total number of steps per day and the total energy expenditure in a sample of office workers in a public university in Malaysia [24].…”
Section: Discussionmentioning
confidence: 99%
“…A survey of employees working in government agencies in the country showed that increasing BMI was linked to lower levels of physical activity [26]. However, it is essential to note that these studies [22, 2426] measured only the steps and physical activity levels of their participants, but not the amount of time spent on MVPA per day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, low intensity PA improves athletic performance, quality of life, and the prognosis of both patients with heart failure and healthy adults [12][13][14] . There are several methods for measuring these physical activities such as self-reported questionnaires, heart rate monitoring, and pedometers [15][16][17][18][19] . Among them, wearable 3-axis accelerometers can measure body movements even at low intensity and use METs to indicate intensity 20,21) .…”
Section: Introductionmentioning
confidence: 99%